Editorial - Reyes-Linero, Alberto (Revista MATUA, 2018)
"The errors and difficulties not solved in the past of mathematics have always been the opportunities of their future" E. T. Bell. We started this edition of the MATUA journal with this phrase that encloses which becomes a motivation for all researchers who are always looking to fill those gaps of the past to open these new doors of the future. This edition of MATUA Journal has authors from countries such as Algeria, Venezuela and Colombia. Researchers experts in educational, applied and pure mathematics. In applied mathematics, topics such as the inclusion in the economic office of renewable energy generation plants are discussed. Educational mathematics topics, such as the social aspects of the teacher's socio-affective strategies in Colombian educational institutions. Pure mathematics topics as an estimate of another case of generalized formula of Gauss-Jacobi square, some inequalities of the Hermite-Hadamard type for Stochastic Processes. These are some of the topics that MATUA magazine has brought in this edition to delight them and to continue persevering in the path of research. We thank the editorial and scientific committee of the magazine, the Vice-Rector for Research of the Universidad del Atlántico for their unconditional support. Also to all the evaluating researchers who collaborated with us with their timely, efficient and quality reviews. We hope you enjoy this publication that is the result of the effort of authors and editorial team. Publisher, Jorge L. Rodríguez Contreras. Alberto M. Reyes Linero.